The orchestra conductor - Pauline Adenot (Transposition)
In musical and social representations, the orchestra conductor is portrayed as a figure of autocratic power, one whose authority is recognized and accepted by all. In reality, however, this authority is a social construct which is created over the course of the rehearsals. Moreover, it is highly dependent on the type of legitimacy held by the conductor, i.e., contractual legitimacy, which remains minimal, or professional legitimacy, which is based on the instrumentalists’ approval and recognition. This article attempts to understand which criteria allow this professional legitimacy to be established, for only this can allow the musicians to truly embrace the conductor’s interpretation.The first part of this article presents our ethnographic study of three symphonic orchestras. The second part distinguishes between contractual legitimacy and professional legitimacy and then explores the process by which the latter is constructed in orchestra-conductor interactions.